2011
DOI: 10.1111/j.1742-481x.2011.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial efficacy of a silver alginate dressing against a broad spectrum of clinically relevant wound isolates

Abstract: Wound dressings impregnated with silver have a role to play in aiding to reduce both the dressing and wound microbial bioburden. It is therefore imperative that antimicrobial wound dressings have efficacy on a broad range of clinical significant microorganisms. Accordingly, this study aimed to determine the antimicrobial efficacy of a silver alginate dressing against 115 wound isolates that had been isolated routinely from patients at West Virginia University Hospital. Standardised corrected zones of inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 27 publications
1
56
0
7
Order By: Relevance
“…It has been found that delay in healing of Wound is due to wound colonization by microorganisms and infections. 3 In case of burn wounds, bacterial infections can frequently which cause of the accumulation of dead tissues, compromised immune system and blood supply 4 . But in In chronic wounds the presence of bacteria persist in an adhesive matrix biofilm form causes more resistant to antimicrobial therapy 5 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been found that delay in healing of Wound is due to wound colonization by microorganisms and infections. 3 In case of burn wounds, bacterial infections can frequently which cause of the accumulation of dead tissues, compromised immune system and blood supply 4 . But in In chronic wounds the presence of bacteria persist in an adhesive matrix biofilm form causes more resistant to antimicrobial therapy 5 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Silver is promising for coating implants as it has a broad spectrum of antibacterial activity against planktonic and sessile Grampositive and Gram-negative bacteria, including multiresistant bacteria (11)(12)(13). Recently, silver coating of central venous catheters (14,15), urinary catheters (16), and ventilator endotracheal tubes (17) has been shown to reduce the infection rate.…”
mentioning
confidence: 99%
“…However, Askina Calgitrol Ag improved the bacteriological status of the wounds. Steven L Percival [72] demonstrated the broad antimicrobial activity of a silver alginate dressing on wound isolates grown in the non-biofilm and biofilm state. It was found that the silver alginate dressing was able to inhibit the growth of all microorganisms tested, including strains of Candida albicans, meticillin-resistant Staphylococcus aureus, S. aureus, vancomycin-resistant Enterococci, Enterococcus faecium, staphylococci and viridans streptococcus.…”
Section: Silver Alginate Dressingsmentioning
confidence: 99%